LESS routine, breaking new ground: New concepts in architectural education - Sträter, Kristina; Schultz-Granberg, Joachim (EAAE Annual Conference Proceedings, 2025)
Architectural teaching is as much about the content that we teach as it is about the tasks and questions that students work on. Against the background of current challenges, it becomes clear that studying architecture should be less about the fulfilment of duties or the achievement of best possible grades. Instead, students are increasingly required to demonstrate a heightened awareness of social responsibility and problem-solving skills. How can lecturers and professors organize curricula so that students are encouraged to take individual responsibility to greater degrees? Which skills are needed to meet the state- of-the-art and future requirements of architectural practice? By its focus on pedagogical concepts, this panel reinforced the cross-sectional character of education for all topical fields in teaching architecture. In the context of the EAAE Congress, we invited contributions on new and unfamiliar pathways and concepts in architectural teaching according to the following topics: Me or us: How do we prepare students for the new challenges they will have to master as future architects? Co-operations: Can pressing issues be solved by a single actor? How important is teamwork and how can it be strengthened? What are the assessment criteria we use to award grades? Is individual grading appropriate and does it motivate students? How can learning be fun? Which project partners do we involve in teaching? Regulations: How do we escape the mania of standardization and guidelines?